Perbandingan angka kejadian low back pain pada buruh suun dan buruh angkat pasir - Made Krisna Wibawa Paramartha; I Gede Eka Wiratnaya; Ketut Gede Mulyadi Ridia (Intisari Sains Medis, 2021)
Background:  Low Back Pain (LBP) is a clinical syndrome that manifests in the form of pain in the 12th rib area and the gluteal folds. Globally, 60% of LBP sufferers are related to work that involves lifting heavy loads. Sandbag-lifters and lifting goods on the top of the head (suun) workers are at risk of suffering from LBP, therefore this connection needs to be investigated further. Aims : This study aims to examine the correlation between occupation, especially lifting sandbags and suun workers with the LBP event among manual laborers in Kumbasari Market, Karangasem, Bali.Method: This study is an observational analytical study using a cross sectional approach. Data were taken using a primary source through the Modified Oswestry Low Back Pain Disability’ questionnaire answers.Result : Totally, there are 50 manual laborers who voluntarily join the study which consist of  25 sandbag lifting workers and 25 suun workers. Respondents’ age ranged According to Body Mass Index (BMI) measurement, most of them (60%) are overweight. In general, 74% manual laborers experienced LBP with the sandbag lifting workers having a higher percentage compared to suun workers (92% vs 56%). Chi-square analysis shows that male gender (r=0.395; p=0.005)., age < 33.6 years old (r=0.296; p=0.037) and working as a sandbag lifter (r=0.633; p=0.000) are correlated with the LBP event.Conclusion : Working as a sandbag lifting workers is correlated with LBP. The other factors that are correlated as well are younger age and male gender. Further longitudinal study needs to be done to assess the risk of LBP.  Latar Belakang: Latar Belakang: Low Back Pain (LBP) merupakan sindrom klinis yang bermanifestasi berupa nyeri di daerah rusuk ke-12 dan lipatan gluteal. Secara global, 60% penderita LBP berhubungan dengan pekerjaan yang melibatkan mengangkat beban berat. Pekerja pengangkat karung pasir dan pengangkat barang di atas kepala (suun) pekerja berisiko menderita LBP, oleh karena itu keterkaitan ini perlu diteliti lebih lanjut.Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan antara pekerjaan khususnya pekerja angkat karung pasir dan pekerja suun dengan kejadian LBP pada tenaga kerja manual di Pasar Kumbasari, Karangasem, Bali.Metode: Penelitian ini merupakan penelitian analitik observasional dengan pendekatan cross sectional. Pengambilan data menggunakan sumber primer melalui jawaban kuesioner Modified Oswestry Low Back Pain Disability.Hasil: Total ada 50 pekerja manual yang secara sukarela mengikuti studi yang terdiri dari 25 pekerja pengangkut karung pasir dan 25 pekerja suun. Rentang umur responden berdasarkan pengukuran Body Mass Index (BMI), sebagian besar (60%) mengalami kegemukan. Secara umum 74% pekerja manual mengalami LBP dengan persentase pekerja pengangkat karung pasir lebih tinggi dibandingkan dengan pekerja suun (92% vs 56%). Analisis chi-square menunjukkan bahwa jenis kelamin laki-laki (r = 0,395; p = 0,005)., Usia <33,6 tahun (r = 0,296; p = 0,037) dan bekerja sebagai pengangkat karung pasir (r = 0,633; p = 0,000) berkorelasi dengan acara LBP.Kesimpulan: Bekerja sebagai pekerja pengangkut karung pasir berhubungan dengan LBP. Faktor lain yang berkorelasi juga adalah usia yang lebih muda dan jenis kelamin laki-laki. Studi longitudinal lebih lanjut perlu dilakukan untuk menilai risiko LBP.